PENGARUH KUALITAS PRODUK DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN KONSUMEN (STUDI PADA KONSUMEN YAMAHA VIXION PT. MATARAM SAKTI SETIABUDI) - Noor Fajar Rizky Nugrahanto; Naili Farida; Sari Listyorini (Universitas Diponegoro, 2015)
The research was motivated by the growth of motorcycle users who become a great opportunity for automotive business players, especially in the field of motorcycles. This growing potential attracted many well - known brands to enliven the motorcycle market in Indonesia. Specially, this research discuss about selling Yamaha Vixion in Mataram Sakti Setiabudi branches that often did not reach the target and even decreased in the period 2011 to 2013. In this case, Yamaha should pay attention to the quality of its products such as Yamaha Vixion and maintain the popularity of the brand, so that consumers feel satisfied and interested in re-purchase. The purpose of this study to determine the effect of product quality and brand awareness on re-purchase decisions through customer satisfaction. This research type is the explanatory, data collection techniques through the questionnaires and interviews. The sampling technique used purposive sampling technique, with a sample of 100 people Data was then analyzed through appropriate qualitative and quantitative analysis techniques, in which the quantitative techniques include validity test, reliability test, correlation coefficient, two-stage regression, coefficient of determination, and significance test ( t test). The research results indicate that the quality of the product (X1) and brand awareness (X2) simultaneously influence consumer satisfaction (Y1) and customer satisfaction (Y1) influence re-purchase decisions (Y2). Based on the results of a two-stage regression, the variable that has the most dominant influence is the quality product (X1). Suggestions in this study that is the Yamaha Mataram Sakti need to open more official workshop in all over areas but specifically for servicing only, Yamaha Mataram Sakti as the dealer needs to sell special tools for service the fuel injection Yamaha Vixion to the public workshops, and if it did not infringe company policy should be able to meet consumer demand for be able to apply the settings on Yamaha Vixion to be more responsive in their usage so that Yamaha Vixion can better satisfy the consumer.